INFLUENCER CHARACTERISTICS, PURCHASE INTENTION, AND BRAND LOYALTY: EVIDENCE FROM ONLINE SHOPPERS IN THAILAND - ปัญญา, ณัฐวุฒิ (Strategic Perspectives on Business and Marketing Management, 2025)
Purpose - Influencer marketing has become a prevalent strategy in digital marketing, particularly on social media platforms. This study investigated the impact of five influencer characteristics (credibility, perceived authenticity, content quality, engagement, and disclosure of sponsorship) on purchase intention and brand loyalty among Thai online shoppers. Design/Methodology/Approach - Using a quantitative research approach, data were collected via an online survey distributed through email, Facebook, Line, and TikTok from 387 consumers who had made purchases from online shops. Multiple regression analyses were employed to examine the relationships between five influencer characteristics and consumer behavioral outcomes (brand loyalty and purchase intention). Mediation test using Baron and Kenny (1986) was also performed. Findings - All five influencer characteristics-credibility, perceived authenticity, content quality, engagement, and sponsorship disclosure-positively and significantly affect purchase intention. Among them, disclosure of sponsorship had the strongest impact (β = .267), followed by engagement (β = .231) and content quality (β = .174). The model explained 42.7% of the variance in purchase intention (R² = .427), demonstrating substantial predictive power. Additionally, the study reveals that influencer characteristics influence consumer behavior both directly (on purchase intention) and indirectly (via brand loyalty). Research Limitation - While this study offers valuable insights into influencer marketing, it has limitations. The model’s R² of .427 indicates that additional variables-such as consumer involvement, product category, social identity, or parasocial relationships-remain unexplored and should be considered in future models. Moreover, the findings are based solely on Thai consumers, whose behaviors reflect cultural traits like collectivism and trust in sponsored content. These factors may not generalize to more individualistic cultures, suggesting the need for cross-cultural studies to improve external validity. Managerial Implication - The findings suggest that clearly disclosing brand partnerships is crucial, as transparency in sponsorship was the most influential factor driving purchase intention. Marketers should also emphasize selecting influencers with strong audience interaction, as engagement significantly boosts consumer responsiveness. Furthermore, investing in the creation of visually compelling and relevant content can enhance both the perceived value of the product and the credibility of the influencer. Originality/Value - The key theoretical contribution of this study lies in its comparison of two competing causal models concerning the relationship between purchase intention and brand loyalty. While the traditional model assumes that purchase intention leads to brand loyalty, the alternative model suggests the reverse- brand loyalty drives purchase intention. The study provides empirical support for the latter, with the alternative model showing significantly stronger explanatory power (R² = .463 vs. .039), reinforcing emerging perspectives in the literature (e.g., Chaudhuri & Holbrook, 2001).